Analysis of Accountability in Increasing Community Satisfaction and Level of Investment Participation Amount of Capital Entering North Penajam Paser Regency - Syarip, Muhammad; Muliyadi Hamid, Hasniaty, (YUME : Journal of Management, 2024)
This research aims to identify accountability practices implemented by the Department of Investment and One Stop Integrated Services (DPMPTSP) North Penajam Paser Regency (PPU) and their relationship with community satisfaction with services and the level of investment participation, which is measured by the amount of capital entering the area. . This research explores how accountability in public services can influence community satisfaction and the extent to which such accountability practices contribute to increased investment in PPU districts.The research method used was a qualitative approach with in-depth interviews with a number of key informants, including the head of the DPMPTSP, the head of the service sector, and the head of the complaints section. Data was collected through interviews, observations, and documentation studies related to accountability practices, complaint management systems, and mechanisms for improving service quality and investment. Data analysis was carried out using interactive model analysis techniques.The research results show that the accountability practices carried out by DPMPTSP Kab. PPU, such as the application of information technology, employee training, and an effective complaint management system, has a positive impact on community satisfaction. The community feels more satisfied with the transparency and ease of accessing services, which in turn increases investment participation in the area. The application of good accountability principles contributes to increasing the amount of incoming capital and makes a significant contribution to local economic development. This research underscores the importance of implementing consistent accountability practices in improving the quality of public services and attracting investment.Keywords: Accountability, Community Satisfaction, Level of Investment Participation